Specific Spiritual and Moral Aspects of Fariduddin Attor’s Creation - Matmuratov Azizbek Abdikarimovich (Genius Journals, 2022)
Sheikh Fariduddin Attar is a great figure of Eastern mystical literature. Such people as Maulana Jalaluddin Rumi and Hazrat Mir Alisher Navoi received spiritual and moral benefits from his Sufi creativity. Remember, you know what happened to six-year-old Alisher after reading “Bird Language”.
Keywords: Sheikh; Maulana; Rumi; Sulayman